2014
DOI: 10.1074/jbc.m113.492777
|View full text |Cite
|
Sign up to set email alerts
|

Dephosphorylation of Barrier-to-autointegration Factor by Protein Phosphatase 4 and Its Role in Cell Mitosis

Abstract: Background: BAF (BANF1) is a highly conserved essential protein that binds nuclear lamina proteins and DNA. Results: Perturbing BAF phosphorylation results in nuclear envelope defects and impaired cell cycle progression. Conclusion: Correct regulation of BAF phosphorylation is essential for its cellular function. Significance: The phenotype resulting from perturbing BAF phosphorylation is strikingly similar to that of a progeroid syndrome resulting from a point mutation in BAF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 39 publications
1
60
0
1
Order By: Relevance
“…Indeed, when CV1 cells were treated with phosphatase inhibitor, increased accumulation of hyperphosphorylated BAF correlating with increased inhibitor concentration could be observed. While these experiments were ongoing, it was discovered that BAF dephosphorylation can be mediated by two phosphatases, PP2A and PP4 (32,34). In this study, we validated that PP2A is a BAF phosphatase and that upon its depletion, phosphorylated BAF accumulated in our CV1 cells as has been described previously (32).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Indeed, when CV1 cells were treated with phosphatase inhibitor, increased accumulation of hyperphosphorylated BAF correlating with increased inhibitor concentration could be observed. While these experiments were ongoing, it was discovered that BAF dephosphorylation can be mediated by two phosphatases, PP2A and PP4 (32,34). In this study, we validated that PP2A is a BAF phosphatase and that upon its depletion, phosphorylated BAF accumulated in our CV1 cells as has been described previously (32).…”
Section: Discussionsupporting
confidence: 85%
“…In support of this model, it has recently been observed that at least two phosphatases, PP2A and PP4, can act on BAF (32,34). Those studies showed that siRNA-mediated depletion of the catalytic subunit of either PP2A or PP4 led to the accumulation of hyperphosphorylated BAF in cell culture and C. elegans (32,34). Therefore, we tested whether BAF phosphatases were capable of modulating BAF phosphorylation, localization, or antipoxviral activity in our cell system.…”
Section: Fig 5 Relocalization Of Baf and Its Mutants To Viral Replicamentioning
confidence: 58%
See 2 more Smart Citations
“…BanF1 localises to the nuclear membrane [206] and is involved in chromatin condensation and nuclear lamina assembly [207,208], cell cycle progression [209]. More recently it has been found to have a direct role in genomic stability, via sister chromatid decatenation following DNA replication [210].…”
Section: (B) Nucleotide Excision Repair (Ner) Pathway and Cisplatin Rmentioning
confidence: 99%